Pengaruh Intensitas Penggunaan Platform E-Commerce Shopee terhadap Perilaku Konsumtif Mahasiswa Generasi Z di Kota Banjarmasin - Nurfitriani Nurfitriani; Dhea Safira Maulaniah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of e-commerce platforms, particularly Shopee, has influenced the consumption patterns of Generation Z students, leading to more consumptive behavior. High usage intensity is assumed to be a key factor driving this change. This study aims to analyze the effect of Shopee e-commerce usage intensity on the consumptive behavior of Generation Z students in Banjarmasin City. This study employs a quantitative approach using a survey method through questionnaires. The research instrument has been tested for validity and reliability. The validity test results indicate that all items in both variables are valid (r-count > r-table 0.161). The reliability test shows a Cronbach’s Alpha value of 0.927 for both variables, indicating high reliability. The normality test using Kolmogorov-Smirnov yields a significance value of 0.200 (> 0.05), indicating normally distributed data. Data analysis was conducted using simple linear regression. The results indicate that the intensity of Shopee usage has a positive effect on students’ consumptive behavior. Higher usage intensity encourages impulsive buying, attraction to promotions, and consumption not fully based on needs. These findings suggest that increased engagement with e-commerce platforms is associated with stronger consumptive tendencies among Generation Z students, highlighting the importance of financial literacy and self-regulation in digital consumption activities.